Some New Directions for Financial Stability? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents the functional responsibilities of a central bank which is required to maintain systemic financial stability without having supervisory oversight of individual financial institutions. Although the Financial Services Authority (FSA) has responsibility for supervising individual financial institutions, the central bank retains responsibility for the smooth running of the domestic payments system and, by extension, oversight of the structure and soundness of the clearing and settlement systems of the main financial markets, money and bond markets, the foreign exchange market, and the equity market. A second, associated function, thrown into prominence by 9/11, is to undertake contingency planning against a major physical disruption of markets, whether by terrorism or natural causes. A third role, perhaps the best-known component in this portfolio of operational tasks, is to provide injections of liquidity, either to the financial system as a whole via open market operations or via lender-of-last-resort (LOLR) actions to individual institutions. A problem with such latter LOLR operations is that they might put taxpayers' money at risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet